Syncretism and Cultural Resilience: The Coexistence and Evolution of Traditional Itolimin and Christian Burial Practices in Esanland, Nigeria - Aluede, Charles Onomudo; Ikhidero, Solomon Ijeweimen (Journal of Contemporary Rituals and Traditions, 2024)
Purpose of the Study: This research aims to uncover how traditional second burial rites coexist with and have adapted to Christian funeral norms, reflecting the socio-religious negotiation in a postcolonial context. Methodology: Employing a qualitative ethnographic approach, the study gathered data through semi-structured interviews with local chiefs, elders, and adults, alongside observations and an extensive review of related literature. Participants were selected based on their deep knowledge of Esan customs and involvement in the Itolimin practice. Main Findings: The study revealed that Itolimin, while embracing certain Christian elements, remains a vital cultural practice that reinforces the community's moral and social order. The rite's evolution showcases the Esan people's ability to blend traditional and Christian values, thereby preserving their cultural identity amidst religious changes. This syncretism illustrates the community's broader cultural resilience and adaptation approach in a rapidly changing religious landscape. Applications of this Study: Insights from this study apply to the broader discourse on funeral practices in postcolonial societies, providing a framework for cultural preservation amidst religious transformation. It is relevant for policymakers and public health officials regarding community health and burial practices. The findings also offer a basis for developing contextual theological education that respects indigenous beliefs within Christian teachings. Novelty/Originality: This study provides a unique contribution to the understanding of funeral rituals within African postcolonial societies by documenting the living tradition of Itolimin. It highlights how syncretism acts as a dynamic cultural force, shaping the way communities like the Esan negotiate identity and religious practice in a contemporary Christian-dominated context.